Strategi Mitigasi Permasalahan Permukiman Kumuh Untuk Mendukung Tercapaian SDGS Tujuan 11 SDGS Tentang Kota Dan Permukiman Yang Berkelanjutan Di Indonesia - Marlina Marlina (Universitas Negeri Gorontalo, 2025)
Urban slum settlements remain one of the most complex and persistent challenges in Indonesia’s urban development landscape. This study aims to examine the characteristics, causes, impacts, and mitigation strategies of slum settlements through a comprehensive literature review. Findings show that slums arise due to rapid urbanization, limited access to affordable housing, weak spatial planning, unclear land legality, and socioeconomic vulnerability among low-income communities. Slum areas are characterized by poor physical conditions, inadequate infrastructure, overcrowding, and limited access to clean water, sanitation, and proper waste management. These conditions contribute to various health, environmental, and social problems that hinder sustainable urban development. The study also highlights the importance of preventive and responsive mitigation strategies, including inclusive spatial planning, provision of affordable housing, community empowerment, in-situ upgrading, and planned relocation for high-risk areas. Furthermore, the successful implementation of national programs such as the KOTAKU Program and the One Million Houses Program requires strong collaboration between local governments, communities, and the private sector. The study concludes that sustainable slum management is essential to achieving SDG 11, which emphasizes inclusive, safe, resilient, and sustainable cities. Strengthened governance, coordinated policies, and continuous community engagement are critical to preventing the emergence of new slums and improving the quality of existing one.